DEVELOPMENT OF WIND-SOLAR MAPS IN AQABA, JORDAN AS POTENTIAL SOURCES FOR POWER GENERATION - Al-Ghriybah, Mohanad; Didane, Djamal Hissein (Journal of Applied Engineering Science, 2022)
The potential for free, clean, and limitless energy from renewable sources has long been recognized. However, because of a lack of thorough wind and solar maps, expertise, and public understanding of the significance of these resources in the country, Jordan continues to rely on non-renewable sources for its energy needs. The main objective of this study is to analyze the potential of solar and wind energies as renewable resources for power generation. Weibull distribution function with two parameters and the Angstrom-Prescott model, respectively, are used in this study to offer estimates of the wind and solar energy in the coastal city of Jordan, Aqaba during a five-year period. According to the assessment of wind potential, the annual means of the shape and scale parameters at 10 m for the studied station varied between (1.65 to 1.73) and (4.42 to 4.86), respectively. During the dry season, the wind speed was seen to be stronger, while during the wet season, it was seen to be slower. The maximum power density is found to be in September with values of 622.81 W/m2 and 192.74 W/m2 for the elevations 80 m and 10 m, respectively. According to the forecast for solar potential in this area, the city’s global solar radiation is promising for the production of solar energy. The maximum global solar radiation is found to be 8.3 KWh/m2 in June. Results also demonstrated that Aqaba city is suitable for wind and solar power generation.